Transcriptomic reprogramming in soybean seedlings under salt stress. (1st June 2018) - Liu, Ailin; Xiao, Zhixia; Li, Man‐Wah; Wong, Fuk‐Ling; Yung, Wai‐Shing; Ku, Yee‐Shan; Wang, Qianwen; Wang, Xin; Xie, Min; Yim, Aldrin Kay‐Yuen; Chan, Ting‐Fung; Lam, Hon‐Ming
Abstract: To obtain a comprehensive understanding of transcriptomic reprogramming under salt stress, we performed whole‐transcriptome sequencing on the leaf and root of soybean seedlings subjected to salt treatment in a time‐course experiment (0, 1, 2, 4, 24, and 48 hr). This time series dataset enabled us to identify important hubs and connections of gene expressions. We highlighted the analysis on phytohormone signaling pathways and their possible crosstalks. Differential expressions were also found among those genes involved in carbon and nitrogen metabolism. In general, the salt‐treated seedlings slowed down their photosynthetic functions and ramped up sugar catabolism to provide extra energy for survival. Primary nitrogen assimilation was shut down whereas nitrogen resources were redistributed. Overall, the results from the transcriptomic analyses indicate that the plant uses a multipronged approach to overcome salt stress, with both fast‐acting, immediate physiological responses, and longer term reactions that may involve metabolic adjustment. Abstract : We performed time‐course experiments to analyse the changes in gene expression profiles in conjunction with physiological adaptations and metabolic adjustments under salt stress. Using multiple time points, we are able to identify important hubs and connections of gene expressions. Our data indicate that soybean seedlings uses a multipronged approach to overcome salt stress, with both fast‐acting, immediate physiological responses, and longer term reactions that may involve metabolic adjustments.